2002
DOI: 10.3386/w9058
|View full text |Cite
|
Sign up to set email alerts
|

Using Discontinuous Eligibility Rules to Identify the Effects of the Federal Medicaid Expansions on Low Income Children

Abstract: This paper exploits the discrete nature of the eligibility criteria for two major federal expansions of Medicaid to measure the effects on Medicaid coverage, overall health insurance coverage, and the probability of visiting a doctor. The "100 percent" expansion, effective in 1991, extended Medicaid eligibility to children born after September 30, 1983 in families below the poverty line. We estimate that this law led to about a 10 percentage point rise in Medicaid coverage for children born just after the cuto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 1 publication
6
90
2
1
Order By: Relevance
“…The goal of the expansions was to increase pregnant women's use of prenatal care and children's access to medical care. The proportion of women of childbearing age eligible for Medicaid coverage of pregnancy-related services more than doubled between 1987 and 1992, and the proportion of children eligible for full Medicaid coverage rose by at least 50% (Cutler and Gruber 1996;Card and Shore-Sheppard 2004). Research has found that the expansions succeeded at increasing both prenatal care and children's medical care, resulting in better birth outcomes and lower child mortality (Currie and Grogger 2002;Gruber 1996a, 1996b).…”
Section: The Effect Of Medicaid Eligibility Expansions On Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the expansions was to increase pregnant women's use of prenatal care and children's access to medical care. The proportion of women of childbearing age eligible for Medicaid coverage of pregnancy-related services more than doubled between 1987 and 1992, and the proportion of children eligible for full Medicaid coverage rose by at least 50% (Cutler and Gruber 1996;Card and Shore-Sheppard 2004). Research has found that the expansions succeeded at increasing both prenatal care and children's medical care, resulting in better birth outcomes and lower child mortality (Currie and Grogger 2002;Gruber 1996a, 1996b).…”
Section: The Effect Of Medicaid Eligibility Expansions On Fertilitymentioning
confidence: 99%
“…2 In addition to reducing health care costs for women and children without health insurance, the expansions may have lowered costs for some individuals already covered by private health insurance. Some people appear to have switched from private insurance to Medicaid during the eligibility expansions (Cutler and Gruber 1996), although estimates of the magnitude of this "crowd-out" effect differ (see Card and Shore-Sheppard 2004). A pronatalist income effect also could have occurred through the extension of Medicaid coverage to older children and concomitant reduction in health care costs for those children.…”
mentioning
confidence: 99%
“…It is common practice for researchers to estimate RD designs by regressing Y on a low-order polynomial in x j , and the treatment indicator D j (e.g., Card and Shore-Sheppard (2004); Kane (2003); DiNardo and Lee (2004); Lee (2006)). If the polynomial function is the correct form for h (·), then conventional least-squares inference is appropriate.…”
Section: Parametric Estimation and Inferencementioning
confidence: 99%
“…Moreover, there is a theoretical consensus that crowdout rates are likely to differ significantly depending on the income criteria specified for eligibility. In the few instances where researchers have examined income (notably Shore-Sheppard 2004), significant differences have been found in coverage and crowd-out across different income levels. To what extent did SCHIP reduce the number of uninsured children, and to what extent did it crowd out private insurance coverage?…”
mentioning
confidence: 99%
“…Recognizing the limitations of the original DID designs, Card and Shore-Sheppard (2004) exploited Medicaid eligibility rules in a regression discontinuity design to identify the effect of two separate Medicaid expansions on low-income children-the 1991 expansion to 100% FPL and the 1990 expansion to children under 6 below 133% FPL. Following the trend of lower estimates, Card and Shore-Sheppard did not find statistically significant crowd-out in either Medicaid expansion.…”
mentioning
confidence: 99%